Paulo Freire y los cincuenta años de la Pedagogía del oprimido - Angues Bambarén, Iván Nelson (2021)
This article aims to show the human centered, social commitment and principles of Paulo Freire, one of the greatest pedagogues of the 20th century. As also a brief synthesis of his main work: "Pedagogy of the oppressed." His work, as well as his methodology, are still valid. His ideas and method continue to be studied and put into practice on the five continents. It is the objective of this work that this great teacher of pedagogy, studied by many educators and the most varied intellectuals in the world, is better known. The aforementioned work has been translated into more than twenty languages and is, without a doubt, the most widely read in the area of education. Likewise, it is also a modest tribute to the author for fiftieth aniversary of the publication in Spanish of the previously mentioned book.